2020
DOI: 10.1136/annrheumdis-2019-216296
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous tanezumab for osteoarthritis of the hip or knee: efficacy and safety results from a 24-week randomised phase III study with a 24-week follow-up period

Abstract: ObjectiveTanezumab, a nerve growth factor inhibitor, was investigated for osteoarthritis (OA) of the hip or knee in a study with 24-week treatment and 24-week safety follow-up.MethodsThis double-blind, randomised, phase III study enrolled adults in Europe and Japan with moderate-to-severe OA who had not responded to or could not tolerate standard-of-care analgesics. Patients were randomised to tanezumab 2.5 mg or 5 mg subcutaneously or matching placebo every 8 weeks (three doses). Co-primary end points were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(180 citation statements)
references
References 31 publications
7
171
0
2
Order By: Relevance
“…Evidence suggests that NGF is a potential target for controlling OA pain. 4,17 Favorable effects 18,28,29 on relationships between estrogen and OA symptoms have been reported. In this paper, we showed that E2 reduces chondrocytes NGF expression significantly, even after stimulation by TGF-β1 or IL-1β.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that NGF is a potential target for controlling OA pain. 4,17 Favorable effects 18,28,29 on relationships between estrogen and OA symptoms have been reported. In this paper, we showed that E2 reduces chondrocytes NGF expression significantly, even after stimulation by TGF-β1 or IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors targeting NGF to relieve OA pain were developed, applied to clinical trials and obtained clinically significant effect. [4][5][6] Nerve growth factor (NGF) is a member of the neurotrophic factors family, which was regarded as a promoter of sensory neuron survival, axonal growth and neurotransmission initially. 7 But later, its crucial role in nociceptor development and pain generation was made out.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another phase III clinical trial evaluated 849 patients with hip and/or knee OA who had not responded to or could not tolerate standard-of-care analgesics. Patients received SC Tanezumab 2.5 mg or 5 mg or placebo every 8 weeks (Berenbaum et al, 2020). The results showed that Tanezumab 5 mg statistically significantly improved pain, physical function and PGA, and Tanezumab 2.5 mg significantly improved pain and physical function, but did not improve PGA (Berenbaum et al, 2020).…”
Section: Monoclonal Antibodies Neutralizing Nerve Growth Factormentioning
confidence: 99%
“…Results from the double-blind, randomized Phase 3 NCT02709486 study of the analgesic efficacy and safety of the SC administration of tanezumab 2.5 mg or 5 mg vs. placebo in patients with OA of the hip or knee were recently reported. 59 In this study, 849 patients received tanezumab or matching placebo (tanezumab 2.5 mg n = 283, tanezumab 5 mg n = 284, placebo n = 282) every 8 weeks for 24 weeks (three doses). The three primary endpoints were (1) change from baseline to Week 24 in Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) Pain, (2) WOMAC Physical Function, and (3) Patient’s Global Assessment of OA (PGA-OA).…”
Section: Antibody Therapeutics Undergoing First Regulatory Review Inmentioning
confidence: 99%